Rancang Bangun Alat Penggulung Kawat Tembaga dengan Kontrol Arduino Nano - Yulanda, Erik Agustian; Fadila, Reza Aditya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to design and implement a copper wire winder with Arduino Nano-based control to enhance efficiency and accuracy in wire winding processes, especially for small and medium industries. The research method includes initial observation, hardware and software design, testing of main components such as the NEMA 17 stepper motor, infrared sensor, and 4x4 keypad, as well as overall system testing. The system was designed to receive winding quantity input via a keypad, control the stepper motor speed using the int delaystep parameter, and display real-time data on an I2C LCD. The results show that the device can wind copper wire with high accuracy, requiring 16 seconds for 25 turns and 34 seconds for 50 turns. Increasing the number of turns demonstrated consistent wire length results aligned with theoretical calculations. However, longer winding durations led to a motor temperature increase of up to 51°C, suggesting the need for operational breaks to prevent overheating. This device provides a practical solution for automating wire winding processes, with potential future developments such as additional safety features and enhanced motor speed to meet higher production demands.